Millimeter-wave power amplifiers - Du Preez, Jaco (Springer, 2017)
This book provides a detailed review of millimeter-wave power amplifiers, discussing design issues and performance limitations commonly encountered in light of the latest research. Power amplifiers, which are able to provide high levels of output power and linearity while being easily integrated with surrounding circuitry, are a crucial component in wireless microwave systems. The book is divided into three parts, the first of which introduces readers to mm-wave wireless systems and power amplifiers. In turn, the second focuses on design principles and EDA concepts, while the third discusses future trends in power amplifier research. The book provides essential information on mm-wave power amplifier theory, as well as the implementation options and technologies involved in their effective design, equipping researchers, circuit designers and practicing engineers to design, model, analyze, test and implement high-performance, spectrally clean and energy-efficient mm-wave systems.
Keywords: Power amplifiers.; Millimeter wave devices.; elektronické knihy; electronic books